Exploring Student Perceptions of climate change awareness: A case study of one University in South Africa - Elijah Osei Manu; Nomxolisi Mtsi; Bulelwa Makena (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
This paper aimed to investigate the awareness of climate change among students at a South African university. Climate change is a global issue resulting from human actions and has significant environmental consequences. Therefore, it is essential to gain an in-depth understanding of the level of awareness among emerging leaders to address climate change effectively. The study employed a qualitative approach with a case study design to explore students' perceptions of climate change awareness. A purposeful sample of eight students was selected for semi-structured interviews. The collected data were analyzed thematically to identify patterns and emerging themes. The findings indicate that students have limited knowledge of climate change, which includes its causes and effects. However, they possess a deeper understanding of adaptation and mitigation strategies. Furthermore, universities fail to address climate change through comprehensive education and awareness campaigns, contributing to students' limited understanding. This study concludes that the lack of awareness and inadequate institutional support contribute to the knowledge gap regarding climate awareness. In addition, a superficial understanding among students as future leaders threatens effective climate action. This conclusion implies that universities must implement strategies to educate and create climate change awareness for students. Consequently, this study recommends universities integrate climate change into their curriculum to promote awareness. In addition, universities should explore pedagogical approaches to deepen students' understanding of interventions to mitigate climate change. Overall, this study contributes to enhancing students' understanding of the impact of climate change.